Peningkatan Kesejahteraan Kelompok Pembuat Dodol Melalui Kegiatan Kampung Bangkit di Desa Bojonggede Bogor - Mohammad Ischak; Wawan Kurniawan; Rina Fitriana; Mustamina Maulani (Lembaga Penelitian dan Pengabdian kepada Masyarakat Universitas Balikpapan (LPPM UNIBA), 2023)
The existence of Micro, Small and Medium Enterprises (MSMEs) is an economic pillar both on a family scale and on a national scale. Even so, there are many problems faced by MSMEs in maintaining and at the same time advancing the business they are engaged in as is the case with the MSME Dodol Making Group in Bojonggede Village, Bojonggede District, Bogor Regency. The problem faced by partners is difficulties during the dodol rolling process, especially when orders are overflowing. Because the rolling process still uses human power, it causes fatigue for workers and has an impact on non-standard products. The second problem is related to the unhealthy condition of the production process room (kitchen) and display area. The Kampung Bangkit Program for Welfare Improvement for the Dodol Group in Bojonggede Village, Bojonggede District, Bogor Regency, aims to increase production as well as improve production facilities and infrastructure that guarantee the health of its workers. The method used is to conduct training on the process of rolling dodol with a simple rolling machine, counseling on Good Manufacturing Practice (GMP) management, and piloting production process infrastructure and facilities through kitchen arrangement. The result of this community service activity is the efficiency and effectiveness of the production process from the processing, packaging, and product display stages. This has a direct impact on increasing production and increasing dodol orders which are felt directly by partners.